The effects of hand soap making practice with addition of pineapple skin extract (Ananas comosus L. Merr) on learning interests in colloidal materials in senior high school - Seriana Zamili; Lisa Ariyanti Pohan; Uswatun Hasanah (Pascasarjana Universitas Negeri Medan, 2019)
Learning by practicum method is a way of delivering learning material by providing opportunities to the students to practicein order to make the students engage in planned and active learning experiences so that students' interest grows on chemistry subject. The population in this study were the students of XI class at YAPSI Senior High School in Medan. The sampling technique is done by using the Quota sampling technique. The instruments were the student’s interests in questionnaire and student activeness observation sheet. The requirements test is in the form of normality test and homogeneity test with the value of Lcount = 0.663 initial interests data and Lcount = 0.172 final interests data which means the data is normally distributed. In the homogeneity test Fcount = 0.233 initial interests data and Fcount = 0.449 final interests data with homogeneous results. The data analysis technique was done by using the hypothesis t test and N-gain test. The results showed that the hand soap making practice with the addition of pineapple extract (Ananas comosus L.. Merr) had an influence on students’ learning interest with N-gain of 7.6 in experimental class data and N-gain of 5.4 in control class data and from the t hypothesis test obtained Tcount> Ttable which Tcount = 6.90 and Ttable at level 0.05 is 2.01 so Ho is accepted, which means that there was an influence of the handsoap making practice with the addition of pineapple skin extract (Ananas comosus L. Merr) on student interests in learning.Keywords: Colloid; hand soap making practice; interests